The level of knowledge about polycystic ovary syndrome and lifestyle among female college students - Wiradhika, Cornelia Bunga; Wijaya, Yosi Maria; Suntoro, Henri (Universitas Airlangga, 2025)
Introduction: PCOS is a global reproductive health problem that often occurs in women of reproductive age. Factors that can influence the occurrence of PCOS include a lack of knowledge about PCOS disease and an unhealthy lifestyle. Knowledge can be defined as something that is known, understood, and applied about PCOS, while lifestyle includes food consumption behaviour, physical activity, sleep rest and stress management. Objective: The purpose of the study was to determine the relationship between the level of knowledge about PCOS and the lifestyle of female students. Methods: The research used a quantitative method with a correlation design through a cross-sectional approach on 196 female college students. Data were collected using two questionnaires, namely the PCOS Knowledge Level questionnaire and the Lifestyle Measurement questionnaire. Data analysis used Chi-square statistical test. Results: The results showed that 172 respondents (87.8%) had good knowledge about PCOS, and 99 respondents (50.5%) had an unhealthy lifestyle. The bivariate analysis's findings indicated a relationship (P-value=0.019) between female students' lifestyle and their degree of PCOS knowledge. Conclusion: The current study offers insightful information about female students' understanding of PCOS and a healthy lifestyle, serving as a resource for further research and directing the creation of successful health promotion campaigns. There needs to be an extensive sharing of knowledge about PCOS risks and preventive actions to lessen its impact on women's health. Keywords: female; knowledge; lifestyle; pcos; polycystic ovary syndrome